2019
DOI: 10.1099/jgv.0.001293
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of a vertically transmitted single-stranded DNA virus in spinybacked orbweavers (Gasteracantha cancriformis) from Florida, USA

Abstract: Spiders (Order Araneae, Class Arachnida) are an important group of predatory arthropods in terrestrial ecosystems that have been recently identified as an untapped reservoir of single-stranded (ss)DNA viruses. Specifically, spiders harbor a diversity of ssDNA viruses encoding a replicationassociated protein (Rep) within a circular genome. However, little is known about the ecology of novel circular Rep-encoding ssDNA (CRESS DNA) viruses. Here we investigated two CRESS DNA viruses recently identified in spinyba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…Coracidia were homogenized in sterile suspension medium buffer through bead beating in a Fisherbrand Bead Mill 4 Homogenizer for 1 min using a mixture of glass beads. Virus particles were purified from homogenates through 0.45 μm filtration and nuclease treatment following methods used to characterize virions isolated from arthropods [29].…”
Section: Virus Purification From Coracidiamentioning
confidence: 99%
“…Coracidia were homogenized in sterile suspension medium buffer through bead beating in a Fisherbrand Bead Mill 4 Homogenizer for 1 min using a mixture of glass beads. Virus particles were purified from homogenates through 0.45 μm filtration and nuclease treatment following methods used to characterize virions isolated from arthropods [29].…”
Section: Virus Purification From Coracidiamentioning
confidence: 99%
“…AdVVVs are single stranded DNA viruses, could transmit vertically to their predators. Recently, researchers found single stranded DNA virus in a spider species, and they suggested vertical transmission of viral partial from prey to the predators [24]. Thus, vertical transmission of virus rises question of food security as crickets commonly used as food and feed.…”
Section: Discussionmentioning
confidence: 99%
“…Circular virus 1, 2, and 3 were the most commonly identified viruses in the surveyed spiders. Rosario et al (2019) found SpOrbCV-1 in all life stages of spinybacked orb weavers, Gasteracantha cancriformis (Linnaeus, 1758). The high prevalence of this virus in all spider life stages suggests SpOrbCV-1 is vertically transmitted, which is the first evidence for a potential vertically-transmitted virus in spiders (Rosario et al 2019).…”
Section: Major Groups That Parasitize Spidersmentioning
confidence: 98%
“…Rosario et al (2019) found SpOrbCV-1 in all life stages of spinybacked orb weavers, Gasteracantha cancriformis (Linnaeus, 1758). The high prevalence of this virus in all spider life stages suggests SpOrbCV-1 is vertically transmitted, which is the first evidence for a potential vertically-transmitted virus in spiders (Rosario et al 2019). SpOrbCV-2 was also identified in spinybacked orb weavers but at a much lower prevalence and only in adults (Rosario et al 2019).…”
Section: Major Groups That Parasitize Spidersmentioning
confidence: 98%